Trend analysis of temperature and rainfall in south gonder zone, anhara ethiopia. - Birhan Getachew (Journal of Degraded and Mining Lands Management, 2018)
This study mainly focuses on exploring trend analysis of temperature and rainfall in the case of south Gonder zone. The analysis is based on the temperature and rainfall variation in south Gonder zone over three stations at Addis Zemen, Nefas Mewcha and Mekane Eyesus. The duration of the study period for temperature and rainfall data was chosen as 1996-2015 for Addis Zemen, 1986-2015 for Nefas Mewcha and 1996-2015 for Mekane Eyesus. The Belg rainfall have been found much more variable (>30%) than the Kiremet rainfall in which the coefficient of variation is greater than 30% over the study area. The findings of the non-parametric Mann-Kendall test revealed that there was no significant trend in the annual and seasonal rainfall data whereas monthly rainfall of April and November shown statistically significant increasing trendover the study area. However, the trend was not significant, the annual, the Kiremet and monthly rainfall during June, August and November shows an increasing particularly November was also statically significant as the computed p-value is less than the significance level α = 0.05.On the other hand, the Belg rainfall and monthly rainfall of March and April shows a decreasing trend. Statistically significant increases of mean annual temperature have been found in Addis Zemen and Nefas Mocha whereas statistically insignificant decrease of mean annual temperature has found in Mekane Eyesus. On the other hand, statistically significant increase of annual maximum temperature has been found in Addis Zemen while statistically insignificant increase of annual maximum temperature have been found for Nefas Mewcha and Mekane Eyesus station. Besides, statistically significant increase of annual minimum temperature has been found in Nefas Mewcha whereas statistically insignificant increase of annual minimum temperature has been found in Addis Zemen and Mekane Eyesus. The rates of change in mean annual temperature for Addis Zemen 1.6980c per 20 years and Nefas Mocha 0.8130c per 30 years have been found greater than the rate of change which was found at national and global level. Therefore, it is recommended that small scale study should be undertaken to clearly detect the rate of climate change and to develop appropriate adaptation strategies for the given agricultural system with the prevailing climatic conditions.